Earnings management and stock returns under different stages of firm life cycle : evidence from Amman stock exchange - Alqerm, Jehad Feras Mustafa (International Islamic University Malaysia, 2014)
This study investigates the impact of earnings management on stock prices in the Amman Stock Exchange under the firm life cycle phenomena. In particular this study examines the two general practices of earnings management: real earnings management (REM) and accounting earnings management (AEM), which might be used by managers to either mislead or inform the external parties. In addition, it examines the information content of earnings management. This study uses a sample of the listed companies in the Amman Stock Exchange in the service and industrial sectors during the period 2001 to 2011. In order to estimate the essential elements of the study, the researcher uses the following models: the adapted modified Jones model (1991) to measure the accounting earnings management (AEM) and the Roychowdhury model (2006) to estimate the real earnings management (REM). Furthermore, Anthony & Ramesh (1992) and the Free Cash Flow (Dickinson, 2011) approaches are used to measure the firm's life cycle. The study uses minimum least square method to test the hypotheses. The findings show that managers tend to use the different techniques of the EM simultaneously and complementarily to reduce the risk of being noticed by the outsiders. Furthermore, the findings reveal that investors are misled by the earnings management practices when they price them positively while they are used opportunistically by managers. On the other hand, the results show that when the role of the firm life cycle on the usage and the pricing of the EM is considered the overall picture is altered. They show that the usage of the EM practices is different over the firm's life cycle. The usage of the EM in the early stages is limited and increases as the firm moves to the later stages. Moreover, the findings show that while the EM practices are positively related to future performance in the early stage of the firm's life, they are negatively related in the later stages. Overall, the findings provide evidence that while managers used earnings management practices informatively in the early stages, and opportunistically in the later stages, the outsiders are unable to capture the different usage of the earnings management and price the two types positively. The findings of this research help investors, regulators, and researchers to locate the hot spot of the firm's life where managers tend to use more of their discretion to manipulate earnings. Furthermore, it sheds light on the compounded usage of the EM and suggests that external parties need to examine all the techniques of the EM before deciding on the level of the manipulation.